Factors affecting adherence in patients with schizophrenia - Siddiqui, Mohd A.; Pattojoshi, Amrit; Khess, Christoday R. J. (International Journal of Advances in Medicine, 2017)
Background: Nonadherence with medication regimens is among the most common causes of psychotic relapse and the need for rehospitalisation. This study was designed to look into the factors affecting attitude towards medication adherence in Schizophrenia and its relationship with severity of illness, side effects of medication. Methods: Adult males and females in the age range of 18-55 years fulfilling criteria for schizophrenia according to ICD – 10, DCR, and reporting at outpatient department were taken up for this study. Severity of illness was assessed by Brief Psychiatric Rating Scale (BPRS), Side effects to medication were assessed by Udvalg for Kliniske Undersogelser (UKU) side effect scale, and Adherence was assessed by Medication adherence rating scale (MARS). Results: Adherence negatively correlated with severity of illness, and side effects in the form of increased sleep duration, asthenia, increased fatigability, lassitude and diminished sexual desire. Regression analysis with MARS as dependent variable showed side effects of medication in the form of increased sleep duration in followed by asthenia, lassitude, and increased fatigability to be predictors of poor adherence in the sample. Conclusions: Poor adherence is associated with severity of schizophrenia, sedation and asthenia like side effects due to medication. Sedation and asthenia like side effects caused a decline in adherence.